Legal Problems of Complex Development of Territories (Part 1) - S. I. Shulzhenko (Управленческое консультирование, 2022)
The article deals with the problems of integrated development of territories in the context of site planning, urban zoning and methods of disposal of public property: privatization, concession agreements, public-private partnerships. Current legislation, including laws of regions of the Russian Federation, was analyzed in detail and gaps in legislation were found. The paper emphasizes the need for further improvement of legislation and law-enforcement practices. The article also focuses on the withdrawal of land plots and objects located on them for the purposes of integrated development of territories and fixing rent rates. Recommendations are provided with regard to changes in existing legislation.